Expression of Connexin 43 in Granular Cell Tumors of the Skin, Tongue and Esophagus - Hermann Kneitz; Verena Frings; Stefan Kircher; Matthias Goebeler (MDPI AG, 2023)
Background: Granular cell tumors (GCT) are rare neoplasms of Schwann cell origin occurring in the skin and in other organs. The etiopathogenesis of GCT is yet poorly understood. Connexin 43 (Cx43) is the most broadly expressed gap junction protein in humans, the tumoral role of which has been investigated in several types of tumors. Its role in GCT of the skin, oral cavity and gastrointestinal tract is as yet unknown. Methods: Herein, we present a study on the immunohistochemical expression of Cx43 in GCT of the skin (n = 15), tongue (n = 4) and esophagus (n = 3). Immunolabeling was scored positive (weak (+), moderate (++) or strong (+++)). Results: Cx43 was expressed by all cases of GCT of the skin, tongue and esophagus (22/22), showing moderate to strong staining. All tissue sections of GCT were characterized by a diffuse, cytoplasmic staining pattern of the tumor cells. None of those showed membranous or nuclear staining. Conclusion: Our results suggest that Cx43 probably plays an important role in the development of this rare tumor entity.